Perception and Signs of Stress among Indonesian University Students: Insights from Rileks Module Responses - Dilfa Juniar; Novika Grasiawaty; Melok Roro Kinanthi (Universitas Muhammadiyah Surakarta, 2025)
Although studies have documented the prevalence of stress among university students, limited attention has been paid to how students define and experience it. This study, part of a larger investigation into Rileks, a culturally adapted web-based stress management program for Indonesian university students, examined how students conceptualize stress and identify its signs. A total of 68 participants, predominantly female and aged between 19 to 42, participated in the study. They were enrolled in undergraduate to doctoral programs and were recruited through convenience sampling via the Rileks study platform. Thematic content analysis was conducted on responses to open-ended questions in the Rileks’ first module, which asked about students' definitions of stress and the signs they experience. Coding was carried out manually using Excel, and inter-rater reliability checks were applied to enhance analytical rigor. Three main themes emerged in students’ definitions of stress: perceived pressure or tension, circumstances exceeding coping capacity, and stress as a state of disruption. A minor theme was stress as a motivating factor. Each main theme encompassed multiple areas of student life, extending beyond academic concerns, and some responses reflected cultural values such as family expectations and societal demands. Students also described signs of stress across four domains: physical, cognitive, emotional, and behavioral. These findings indicate that students’ perceptions of stress may shaped by personal and contextual factors, offering practical implications for enhancing early recognition and communication of students’ stress through approaches that are both relevant and culturally sensitive.